Beyond Janus Geometry: Characterization of Flow Fields around Nonspherical Photocatalytic Microswimmers. Issue 24 (15th July 2022) - Heckel, Sandra; Bilsing, Clemens; Wittmann, Martin; Gemming, Thomas; Büttner, Lars; Czarske, Jürgen; Simmchen, Juliane
Abstract: Catalytic microswimmers that move by a phoretic mechanism in response to a self‐induced chemical gradient are often obtained by the design of spherical janus microparticles, which suffer from multi‐step fabrication and low yields. Approaches that circumvent laborious multi‐step fabrication include the exploitation of the possibility of nonuniform catalytic activity along the surface of irregular particle shapes, local excitation or intrinsic asymmetry. Unfortunately, the effects on the generation of motion remain poorly understood. In this work, single crystalline BiVO4 microswimmers are presented that rely on a strict inherent asymmetry of charge‐carrier distribution under illumination. The origin of the asymmetrical flow pattern is elucidated because of the high spatial resolution of measured flow fields around pinned BiVO4 colloids. As a result the flow from oxidative to reductive particle sides is confirmed. Distribution of oxidation and reduction reactions suggests a dominant self‐electrophoretic motion mechanism with a source quadrupole as the origin of the induced flows. It is shown that the symmetry of the flow fields is broken by self‐shadowing of the particles and synthetic surface defects that impact the photocatalytic activity of the microswimmers. The results demonstrate the complexity of symmetry breaking in nonspherical microswimmers and emphasize the role of self‐shadowing for photocatalytic microswimmers. The findings are leading the way toward understanding of propulsion mechanisms of phoretic colloids of various shapes. Abstract : BiVO4 single crystal microswimmers swim through a degradation of peroxide without a specific asymmetrization step. Particle tracking velocimetry gives access to the flow pattern enabling the motion.